2021
DOI: 10.1111/ejh.13599
|View full text |Cite
|
Sign up to set email alerts
|

Safety of apixaban compared to warfarin in hemodialysis patients: Do antiplatelets make a difference?

Abstract: Background Data on the safety of apixaban compared to warfarin in hemodialysis (HD) patients are accumulating, but the impact of concomitant antiplatelet use is unknown. Objectives Compare hemorrhagic risk and impact of antiplatelets in HD patients receiving oral anticoagulants (OAC). Methods Retrospective, multi‐center study of HD patients started on OAC inpatient over 5 years. Results 707 patients were included: 563 received warfarin, and 144 received apixaban. 197 had bleeding, most in the warfarin group (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…Our group recently reported findings from a retrospective analysis of bleeding rates in HD patients treated with either warfarin or apixaban [33]. We found a significantly lower bleeding propensity with apixaban use alone compared to warfarin alone, whereas concurrent antiplatelet therapy markedly reduced the difference (Figure 1).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Our group recently reported findings from a retrospective analysis of bleeding rates in HD patients treated with either warfarin or apixaban [33]. We found a significantly lower bleeding propensity with apixaban use alone compared to warfarin alone, whereas concurrent antiplatelet therapy markedly reduced the difference (Figure 1).…”
mentioning
confidence: 77%
“…Chiefly, analyses of bleeding risk with DOACs in CKD and HD patients have largely ignored the interaction of antiplatelets and anticoagulants, which has recently gained attention in the cardiovascular disease literature. As previously discussed, CKD and HD patients are underrepresented in these studies, but the importance of this issue is underscored by a high percentage of antiplatelet use (40%-50.6%) in our cohort and that of others [32,33]. In the RENAL-AF trial, the impact of antiplatelet therapy on bleeding, despite a high rate of use (40%), was not explored.…”
mentioning
confidence: 86%
“…38,39 Of the 8 remaining retrospective studies, 4 reported efficacy data between DOAC therapy and warfarin, and only 1 found a difference in favor of DOAC therapy. 37,40,41,43 Additionally, Miao et al 46 reported no difference between apixaban and rivaroxaban. Despite a lack of efficacy data, safety outcomes favor DOAC use in patients with AF and CKD-5 or ESKD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of efficacy data, safety outcomes favor DOAC use in patients with AF and CKD-5 or ESKD. 40,43,44 To date, no study has reported greater rates of bleeding with DOACs compared to warfarin. 40,43,44 Likewise, no single DOAC has been established as safer than any other in CKD-5 or ESKD, although most comparisons between DOACs are with apixaban and rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation